PERAN GURU DALAM MEWUJUDKAN MERDEKA BELAJAR MELALUI PEMBELAJARAN BERDIFERENSIASI DI SDN TUGU 10 DEPOK - Jessica Triuli Adelia; Prayuningtyas Angger Wardhani; Juhana Sakmal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of Merdeka Belajar emphasizes learning freedom that respects students’ diverse characteristics, which cannot be achieved without the active role of teachers. However, in practice, teachers still face challenges in accommodating students’ varied readiness, interests, and learning profiles. This study aims to explore the role of teachers in realizing Merdeka Belajar through differentiated instruction at SDN Tugu 10 Depok. The research employed a qualitative approach using a phenomenological study design. Data were collected through classroom observations, in-depth interviews with teachers, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The results indicate that teachers play a significant role as planners, facilitators, motivators, and evaluators in implementing differentiated instruction. Teachers conduct diagnostic assessments, design learning activities based on students’ needs, implement differentiation in content, process, and product, and carry out continuous assessment. The implementation of differentiated learning creates an engaging learning environment, increases student participation, and supports students’ independence in learning. Differentiated learning is an effective strategy to realize Merdeka Belajar when supported by teachers’ pedagogical competence, reflective practices, and flexibility in learning design.